2017
DOI: 10.1111/dmcn.13481
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of childhood selective dorsal rhizotomy on pain, fatigue, and function: a case–control study

Abstract: Aim Selective dorsal rhizotomy (SDR) is a surgical treatment for spasticity in children with cerebral palsy (CP). Studies suggest long-lasting effects of SDR on spasticity; long-term effects on symptoms and function are not clear. This study tested whether adults with CP (average 22y after SDR) report less pain, fatigue, and functional decline than a retrospectively assessed non-surgical comparison group. Method This was a case–control study. Eighty-eight adults with CP (mean age 27y 0mo; SDR=38; non-surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 27 publications
2
29
0
1
Order By: Relevance
“…One study had controls of comparable age, but the SDR and comparison group were significantly different with respect to Gross Motor Function Classification System (GMFCS) level. Moreover, the comparison group included individuals with all subtypes of CP, even subtypes purposely excluded from SDR intervention, such as dyskinetic and unilateral CP . In the other investigation with a control group, Munger et al made retrospective comparisons (indicated by a propensity model to be highly accurate) to individuals whose clinical presentation was appropriate for SDR, but who, for a variety of reasons, did not undergo surgery .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study had controls of comparable age, but the SDR and comparison group were significantly different with respect to Gross Motor Function Classification System (GMFCS) level. Moreover, the comparison group included individuals with all subtypes of CP, even subtypes purposely excluded from SDR intervention, such as dyskinetic and unilateral CP . In the other investigation with a control group, Munger et al made retrospective comparisons (indicated by a propensity model to be highly accurate) to individuals whose clinical presentation was appropriate for SDR, but who, for a variety of reasons, did not undergo surgery .…”
Section: Resultsmentioning
confidence: 99%
“…Included studies for outcome of SDR at 10 years or more After removing duplicates, 199 articles were screened and 16 included [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (Table II and Fig. S1); none involved a randomized control trial nor prospective evaluation of a control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concluíram que o grupo RDS apresentou menos dor, fadiga e declínio funcional comparado com o grupo não-cirúrgico. 40 A técnica de RDS por laminoplastia de segmento único fornece uma abordagem menos invasiva e a incidência de escoliose após esta abordagem é comparável com a história natural de crianças acompanhado ambulatoriamente. 41…”
Section: Descrição Da Técnicaunclassified